(untitled) (Bangladesh Journal of Agriculture, 2023)
Growth and instability of crops are two crucial aspects that significantly impact the agricultural sector and its contributions to enhancing agricultural resilience, food security, economic development, risk management, income volatility, and sustainable practices to meet increasing demands and challenges precipitated by erratic weather patterns. Black gram is one of the high-value pulses in Bangladesh and is essential for human nutrition and sustaining agricultural soil quality. This study presents the growth and instability in area, production, and yield of black gram along with the contributory factors affecting the growth and instability of black gram production in the context of Bangladesh’s agricultural landscape based on secondary data for the last 40 years (1981-2020). The entire period was divided into four sub-periods: 1981-90, 1991-2000, 2001-10 and 2011-20 for analysis through different statistical tools. Growth rates were calculated by fitting an exponential growth function, and instability was analyzed by generating the Cuddy-Della Valle index. The analysis presented highlights a significant decrease in the area of black gram cultivation and production, even though there has been a notable increase in black gram yields. However, this increase in yield is not sufficient to meet the overall demand for black gram in the country. The study also points out that the growth rate of yield is low compared to the increase in demand. Throughout the study period, the contribution of the area was -3.29%, while the yield contribution was 142.25% in the average growth of black gram production at the national level. The analysis underscores the lack of stability in black gram cultivation, production, and yield during this period. Notably, there were instabilities of 4.37%, 4.89%, and -25.7% in the area, production, and productivity of black gram at the national level, respectively. Hence, researchers, policymakers, and farmers must prioritize advancing technology to boost black gram production. This enhancement holds the promise of improving food security in Bangladesh. Encouragingly, there are signs that the government has recently implemented incentives to support the cultivation of black gram. Bangladesh J. Agri. 2023, 48(2): 30-38